Effect of Sodium Iron EDTA Fortification in Tempe in Serum Iron and Ferritin Level of Anemic Female Wistar Rats - Sudargo, Toto; Kusuma, Rio Jati; Arjuna, Tonny; Hasnawati, Rasita Amelia; Rubi, Dianandha Septiana; Rohman, Abdul (Pakistan Journal of Nutrition, 2015)
In Indonesia, the prevalence of iron deficiency anemia is still high. Iron fortification in food using sodium ferry EDTA (NaFeEDTA) potentially reduce the incidence of iron deficiency anemia. Iron deficient anemia was induced in female Wistar rats by feeding low iron (Fe) diet and was randomly divided into ten groups where one group was fed normal diet which serves as control group. Every treatment group will receive FeSO4, tempe and iron-fortified tempe (temFe) with iron dosage of 6, 12 and 24 ppm respectively for 17 days. Blood was drawn for serum iron (SI) and serum ferritin (SF) measurement. After treatment, temFe 24 ppm group has the highest SI and the highest SI changed compared with other treatment groups although no significant different (p>0.05) was observed between temFe 24 ppm group and FeSO4 24 ppm group for SI (139.36±1.58 vs 134.10±2.73 μg/dL) and SI changed (89.40±2.78 vs 84.47±2.41 μg/dL). SF was increased in all treatment diet with the highest was found in FeSO4 24 ppm group (73.25±3.16 ng/mL). However, SF level wasn’t significantly different between the FeSO4 24 ppm, tempe 24 ppm and temFe 24 ppm and group (p>0.05). Iron fortification in tempe with NaFeEDTA will restore both SI and SF in iron deficiency anemia.